A suggested outline for the introduction of nutrition education at primary level in Jamaica - Hamilton, Marlene A. (UNESCO, 1983)
This material was presented at the International Conference on Nutrition Education, Oxford, England, 1977. It describes a method of incorporating nutrition education into the primary curriculum as a part of, and not in addition to, the existing curriculum. Specific content links are identified. The necessity for a practical approach, for the encouragement of positive attitudes to nutrition education, and for placing in the primary system the prerequisites for work at the secondary level are emphasized
Keywords: Nutrition education